Translanguaging in the development of EFL learners' foreign language skills in Turkish context - Yasar Yuzlu, Muhammet; Dikilitas, Kenan (Innovation in language learning and teaching, 2022)
This study investigates the potential impact of translanguaging pedagogy on EFL learners' four language skills, as well as their perceptions towards its in-class implementation as a pedagogy. The study was conducted for 10 weeks with 60 pre-intermediate and 60 upper-intermediate students at a high school in the north of Turkey. In each group, half of the students were assigned as the experimental group, while the other half as the control group. The experimental groups were subject to a 10- week (40 h of teaching) of translanguaging pedagogy, whereas one of the control groups was taught through grammar-translation methods, while the other, through communicative language approach. In the study, the quasi-experimental mixed methods design was employed. The analysis of a paired-sample t-test and one-way analysis of ANCOVA indicated that translanguaging played an effective role in improving students' four English language skills. Semi-structured interviews revealed that the students reported constructive, cognitive, interactive, and affective benefits through translanguaging pedagogy since they were able to draw upon all the linguistic resources for meaning-making and negotiation, a sense of comfort, and a sense of motivation to use English. We offer implications for teachers and teacher educators regarding the role of translanguaging in teaching English.